Liver abscess mimicking tumor: A pediatric case report (2020)
A case report of a 3-year-old boy with past medical history of intestinal partially treated amebiasis, is presented. The patient was admitted to Pediatric Unit, San Cristóbal Central Hospi- tal, Táchira, Venezuela, with abdominal pain and fever. An abdominal bloating and a 3 cm palpable hepatomegaly below the right costal margin were assessed. Abdominal ultrasound revealed a liver enlarged in the right antero-superior area. A rounded space-occupying lesion, predominantly solid, with mixed-echo patterns, was assessed using ultrasound. The preliminary diagnosis issued was of acute medical abdomen with hepatic space-occupying lesion considered amebic liver abscess or liver tumor, moderate hypochromic microcytic anemia, and malnutrition with short stature. During the case evolution, a frst computerized tomography exploration was necessary in order to exploit the capacity of this imaging tech- nique to scan an abscess as a peripheral pseudo-capsule showing rim enhancement. Nevertheless, this theoretical shape associated with abscesses on computerized tomog- raphy scans was unable to verify in this study. At this point, the mixed-echo patterns of the preliminary ultrasound study and the imprecision of the computerized tomography scan to categorize the lesion as an abscess or a tumor, do not allow establishing a defnitive diagnosis. A management based on antibiotic therapy is then proposed. The progression of the space-occupying lesion was performed using ultrasound and computerized tomography scans during the clinical evolution. The imaging controls probe a slight decrease of the liver le- sion, which is diagnosed as a liver abscess. Percutaneous transhepatic drainage was performed. An amoebic liver ab- scess in resolution was fnally diagnosed.